Development of the optimal scheme for the synthesis of the dipeptide TSPO ligand, N-phenylpropionyl-L-tryptophanyl-L-leucine amide (GD-102), a potential anxiolytic drug - O. A. Deeva (Фармакокинетика и Фармакодинамика)
Previously at the Zakusov Research Institute of Pharmacology the first dipeptide ligand TSPO, the compound N-phenylpropionyl-L-tryptophanyl-L-leucine amide (laboratory code GD-102), was designed and synthesized. The anxiolytic activity was detected for this compound at the doses 0.01–1.0 mg/kg intraperitoneally (ip) in mice. Dipeptide GD-102 also possessed antidepressant-like activity at the doses 0.01 and 0.05 mg/kg ip in BALB/c mice in the Porsolt forced swim test. The ligand properties of dipeptide GD-102 to TSPO were confirmed by pharmacological inhibitory analysis and molecular docking. This work is devoted to the development of the optimal scheme for the synthesis of the GD-102. 3 methods were tried — 1 activated succinimide esters method, 2 activated pentafluorophenyl ethers method and 3 imidazolide method. These three synthesis schemes have been compared in terms of yield and optical purity of the final product. It was shown that the optimal synthesis scheme is the first one, using succinimide esters.